PELATIHAN VISUALISASI DATA SEKOLAH SMK SEPULUH NOPEMBER SIDOARJO - Athoillah, Muhammad; Pramesti, Wara; Lusyanti Gili, Ireni; Findiariska, Yasmin (Universitas PGRI Adi Buana Surabaya, 2022)
As a form of scientific implementation in a proactive, consistent and sustainable manner in providing the maximum benefit to the community through the development of science, especially in the field of data science. The Statistics Study Program at PGRI Adi Buana University Surabaya in collaboration with the Institute for Research and Community Service (LPPM) at PGRI Adi Buana University Surabaya provided training on visualization of school data at SMK Sepuluh Nopember. This data visualization training is needed because of the school's need for the ability to process data properly so that the information conveyed by the data can be conveyed properly by the reader. The training activities were successfully carried out as seen from the evaluation results of the pre-test and post-test scores which increased significantly. In addition, the success of the activity can also be seen from the feedback of participants who want continuous training.